« Mon fils, c’est ma petite entreprise ! » Les parcours des enfants autistes entre carence de soins et inégalités sociales en Seine-Saint-Denis - Brigitte Chamak; Béatrice Bonniau (Anthropologie & Santé)
The role of the family, and in particular of mothers, in managing the health and education of children has been frequently demonstrated. In the case of autism, this commitment, and the accompaniment of the children concerned are even more obvious. Bringing up an autistic child can have a considerable impact on family life in terms of stress, employment, isolation and financial constraints. The day-to-day difficulties experienced by all parents are compounded by socio-economic disparities. In order to illustrate the obstacles strewn on the pathway for the care and schooling of autistic children, we have chosen to focus on the experiences of families concerned and on the systems set up to cater to these children and their parents in the Parisian suburban area of Seine-Saint-Denis, a district with a large population and where the shortage of places and means is encountered in both the private and the public sector.